How to be an ecological economist - Faber, Malte (Discussion paper series, 2007)
To answer the question "How to be an Ecological Economist", we must start by defining the field of Ecological Economics. Mainstream Economics altogether lacks the concepts required to deal adequately with nature, justice and time. It was the absence of these three concepts in this otherwise great social science that led to the establishment of Ecological Economics. The interest in nature, justice and time is its defining characteristic. The main thesis of this paper is that our field is a fragile institution and that the professional existence of an ecological economist is no less fragile. However, this very fragility also represents freedom, scope for free thinking, conceptualising and research. Nevertheless, to be able to really use and in turn enjoy the full scope of this freedom, an ecological economist needs certain specific characteristics, in particular what is termed in the German philosophical tradition "Urteilskraft" and in English "power of judgement". A description of these characteristics is developed in this paper, providing an answer to the question "How to be an ecological economist?"
Keywords: Arbeitspapier; Graue Literatur